CA 125 dan Pemakaian Klinis Dalam Penatalaksanaan Kanker Ovarium - Dwi ariningtyas, Ninuk (Qanun Medika - Medical Journal Faculty of Medicine Muhammadiyah Surabaya, 2018)
Today there are three types of ovarian cancer, namely epithelial cell tumors (70%), which are the largest part of the tumor, Germ cell tumors with a smaller frequency, and sex cord-stroma tumors which is the smallest proportion of about 8% of neoplasm. Ovarian cancer is characterized by unusual early symptoms, real symptoms at advanced stages and low survival rates. Therefore, ovarian cancer is the leading cause of death from gynecological cancer. Over the past decade, several studies have been directed at increasing outcomes of ovarian cancer by performing preclinical screening tests, determining the early stages of disease by using radiological examination or tumor marker serum. The purpose of screening for ovarian cancer is to reduce mortality by detection of stage 1 ovarian invasive epithelial cancer that is potential to be cured. Serum CA 125 measurements are often used to monitor disease status or predict residual disease. A number of cell surface antigens and serum proteins are produced by ovarian tumors and can be tested with monoclonal antibodies. Some of these tests have been clinically applied as a marker of disease and are useful in the detection of subclinical diseases and the diagnosis of recurrent ovarian cancer. Among the multiple biochemical markers in ovarian cancer, the most studied are CA 125. CA 125 is a surface glycoprotein detectable cells in more than 80% of cases of ovarian epithelial cancer. This test is clinically used in the evaluation of mass diagnostics in the ovaries, observation of response to treatment, and further evaluation of patients with ovarian cancer